Perlindungan Hukum Hak Cipta Terhadap Musik Di Indonesia Yang Di Upload Di Media Massa - Zakariya, Hafid (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
In this era of globalization, people are pampered with any technology made easy with technological developments. With this technology able to create many opportunities one of them for the development of music in Indoneisa with social media in Indonesia can be rapidly spread and can be accessed by everyone so that the music can be Opportunities for artists to be commercialized. But with these developments many Parties are not responsible by doing music piracy by downloading so as to save or record with recording technology and storage nowadays, such as Memory card or flash disk with different types of brands. The advancement of storage technology has made it easier for users to record or duplicate a large number of creations that appear on internet media with ease and cheap cost even free, thus it does not comply with article 9 paragraph (3) UUHC Number 28 Year 2014: Any person without permission the creator or copyright holder is prohibited from making a reproduction and/or commercial use of the creation. And article 4 Law No 28 year 2014 part of article by article is a right that is only intended for the author, so that no other party can exploit that right without the permission of the creator. Copyright holders who are not creators only have a portion of the exclusive right of economic rights. Legal protections that government grants to songwriters or rights holders are now in two ways, first being a site blocking that is deemed to commit copyright infringement despite not running maximally and not reducing The occurrence of violations, and the second is to socialize both the songwriters or the rightsholders on the importance of registering the creation, as well as to the public about the culture respecting the work of the nation for law enforcement rights Intellectual property can be implemented well and currently the government has established a new institution of non-Ministry called Creative Economic Agency (BEKRAF). The liability made by the provider of free download sites is not compliant with the law. Providers of illegal sites even circumcarent their existence as illegal sites by way of positioning itself as a song search site that does not upload songs in the site but rather equate its site with search sites such as Google and Ymail.